Citizens' Europe: Crowded out by economic focus - Heather Grabbe; Henning Meyer; Diego Valiante (Intereconomics, 2012)
Over the last ten years the European unification project seemed to rely overwhelmingly on progress in economic terms. The most prominent achievements - the Single Market, the harmonisation of market regulation, the euro - were all driven by an economic rationale. However, attempts to rescue Europe from the ongoing financial crisis call for mutual support and solidarity, concepts that can hardly be derived from pure economic reasoning. This leads to an important question that has been too long neglected: what is the political and civic motivation for a united Europe? Besides a great desire to stabilise peace in Europe, the origins of the unification activities also included mutual interest in language, culture, habits and people in neighbouring countries. Has this been abandoned in favour of a purely economic vision? Or are the economic arguments merely the easiest to promote to the European population? What message does this send in times of mistrust in markets and dim economic prospects for the eurozone? Can a political, cultural and civic European spirit still be reinvigorated, and if so, how?
Keywords: 330; Staatsangehörigkeit; Partizipation; Europäische Wirtschafts- und Währungsunion; Demokratie; EU-Staaten